Home Visit: Psychological Strengthening Between Schools and Student Guardians in Early Childhood Education - Wahyu Sri Lestari, Dian (International Proceedings of Nusantara Raya, 2023)
Three environments that exert a major influence in educating children are family, school and community. The three environments have a mutually defining relationship in every stage of child development, especially when still at an early age. The assumption of parents who fully entrust children's development to school, lack of knowledge about stimulating children's growth and development, and the difficulty of educating and teaching children to learn at home requires collaboration with the school so that there is harmony and synergy in accompanying children's growth and development. This study aims to determine the technical and impact of home visits designed by the school. The method used in this study is a qualitative method that is descriptive, meaning that the results of this study are presented by presenting data obtained from the identification results of one of the school's leading activities, namely home visits. Data collection techniques through interviews, observation, and documentation. Data analysis techniques are carried out by reducing data, presenting data, and drawing conclusions or verification. The results of the study concluded that the home visit program in ECCE can provide psychological reinforcement for parents and students by providing structured and planned support, guidance, checking, and mentoring personally and directly in the home environment as a familiar and familiar environment for children and their families. This is one of the effective ways to optimize the learning process in ECCE and provide significant benefits for students, teachers and parents.